2016
DOI: 10.1002/14651858.cd011715.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Remote versus face-to-face check-ups for asthma

Abstract: Current randomised evidence does not demonstrate any important differences between face-to-face and remote asthma check-ups in terms of exacerbations, asthma control or quality of life. There is insufficient information to rule out differences in efficacy, or to say whether or not remote asthma check-ups are a safe alternative to being seen face-to-face.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 93 publications
0
44
0
1
Order By: Relevance
“…27 Furthermore, two recent meta-analyses have demonstrated no differences in asthma outcomes between telemedicine and face-to-face visits for asthma in children and adults. 28,29 The meta-analyses included very few studies that utilized the integrated approach demonstrated in this study with VBT medical and self-management visits and electronic inhaler monitoring in adolescents living in economically disadvantaged neighborhoods and the majority of studies were conducted in rural or remote settings or enrolled young children. [30][31][32][33][34]…”
Section: Discussionmentioning
confidence: 99%
“…27 Furthermore, two recent meta-analyses have demonstrated no differences in asthma outcomes between telemedicine and face-to-face visits for asthma in children and adults. 28,29 The meta-analyses included very few studies that utilized the integrated approach demonstrated in this study with VBT medical and self-management visits and electronic inhaler monitoring in adolescents living in economically disadvantaged neighborhoods and the majority of studies were conducted in rural or remote settings or enrolled young children. [30][31][32][33][34]…”
Section: Discussionmentioning
confidence: 99%
“…Lung function assessed by means of forced expiratory volume in the first second (FEV1) was only reported in one study. The authors of this review 10 Total number of exacerbations was only analyzed in one RCT, with borderline statistical significance (P = 0.06). In another trial, it was reported that the mean number of exacerbations per month was significantly higher among the controls than in the telehealthcare group (0.78 ± 0.77 and 0.23 ± 0.38, respectively; P < 0.0001).…”
Section: Remote Check-ups For Asthmamentioning
confidence: 94%
“…As for the situations in which medical teleconsultation can be indicated, this review identified 11 studies that addressed specific conditions, 7 of which used video teleconsultation and the other three used the electronic consultation system or a combination of video and telephone or even video, phone and email. Studies that compared medical teleconsultation by video with faceto-face consultations identified equivalent results regarding glycemic control of individuals with diabetes 39 , as well as in exacerbations, disease control and quality of life of patients with asthma 34 and in the treatment of childhood obesity 37 . High rates of satisfaction were also identified among patients treated for rheumatological diseases 47 and better experience of care and health outcomes in nephrology care 35 .…”
Section: Teleconsultation Indicationsmentioning
confidence: 99%
“…However, in the latter case, the authors warned about being careful in generalizing the results 23 . Other studies also indicate the need for future studies 30,34,47 , with a promising potential 37 .…”
Section: Teleconsultation Indicationsmentioning
confidence: 99%